(untitled) (Journal of Applied Learning and Teaching, 2022)
Singapore higher education’s intraperiod response to the novel coronavirus (COVID-19) pandemic was unique compared to other countries, being praised by the World Health Organisation (WHO) for its early response. Like many other countries, alarming growth in cases appeared, and careful strategies for the continuation of learning were implemented. This paper provides a critical case study and reflection-in-action (Green et al., 2020) of the Singaporean intraperiod response, exploring individual responses from a sample of six autonomous universities, two international universities with campuses in Singapore, and four Private Education Institutions. Through a defined qualitative content analysis of university documentation, scant academic literature, and government and media sources, an understanding of the pandemic response in Singapore was possible. We chose to ensure full coverage of the city-state to enable a comprehensive country analysis in contrast to the growing volume of single-institution pandemic and emergency remote teaching case studies applying a sociotechnical theoretical framework to guide an analysis between educational technology systems and the people using it to teach, work, and learn. This study identified that while tasks and technology were presented with depth, the social elements – people and systems – were often lacking accurate description. We discuss how this technical focus has practical and research implications, and how future research and university teaching and learning practice can better respond to future challenges through reflection of the sociotechnical perspective.